Strength properties of engineered wood i-joist with finger jointed oriented strand board (osb) web and laminated veneer lumber flanges (lvl) / Wan Mohd Nazri Wan Abd Rahman and Mohd Ariff Jamaludin - Wan Abd Rahman, Wan Mohd Nazri; Jamaludin, Mohd Ariff (Universiti Teknologi MARA Cawangan Pahang, 2000)
Engineered wood I-joist is a system that consists of flanges and web components. Both components have to work together as a system in order to match the strength property of solid wood beam. This study was carried out with the objective of obtaining the strength properties of I-joist made from finger jointed oriented strand board (OSB) web and 2 types of flanges (solid wood and laminated veneer lumber). OSB is recognized as a less costly, structural equivalent alternative to sheathing plywood for use in new home construction. The result showed that the average of modulus of rupture (MOR) of solid timber flanges (37.89 MPa) was higher than I-joist with LVL flanges (31.42 MPa). It was observed that failures in all of the I-joist specimens studied were either in tension or in compression. For specimens of solid timber flanges and LVL flanges, the failure occurred at the web joints. OSB web can be produced from the off-cuts of tertiary processing mills that use OSB for other consumer products. Hence, the full use of off-cuts would consequently increase the recovery rate and the net profit. This study could lead to the utilisation of wood residues from an OSB plant as an alternative raw material for the production of web component in I-joists system.